Building Information Modeling (BIM) Capabilities in the Operation and Maintenance Phase of Green Buildings: A Systematic Review - Yu Cao; Syahrul Nizam Kamaruzzaman; Nur Mardhiyah Aziz (Buildings, 2022)
In recent years, green buildings have gradually become a worldwide trend. Compared with traditional buildings, green buildings have advanced requirements and standards in their operation and maintenance phase. In such a context, some studies proposed that building information modeling (BIM) is an effective method to improve green buildings’ operation and maintenance quality. The aim of this study is to perform a comprehensive review of the BIM capabilities in the operation and maintenance phase of green buildings through a systematic literature review. To achieve this aim, the PRISMA protocol was used to perform this systematic review. The whole systematic review was conducted between January 2022 and April 2022: 128 articles were included. In the process of study, Web of Science (WoS) and Scopus were adopted as bibliographic repositories. Through this study, it can be determined that BIM capabilities can be utilized in the facility management of the green building in the following aspects: safety and emergency management, maintenance and repair, energy management, security, retrofit and renovation, space management, and asset management. Secondly, these BIM capabilities were discussed, and the challenges and shortcomings of BIM capabilities in the operation and maintenance phase of green buildings were reviewed. Finally, a comprehensive overview of BIM capabilities in the facility management of green buildings was developed, and suggestions for future study were provided.